2013
DOI: 10.1002/cncr.28393
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of risk models and molecular diagnostics to permit personalized management of cancer

Abstract: Despite the advances made in cancer management over the past few decades, improvements in cancer diagnosis and prognosis are still poor, highlighting the need for individualized strategies. Toward this goal, risk prediction models and molecular diagnostic tools have been developed, tailoring each step of risk assessment from diagnosis to treatment and clinical outcomes based on the individual's clinical, epidemiological, and molecular profiles. These approaches hold increasing promise for delivering a new para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…The C-index ranges from 0.0 to 1.0, with the higher value indicating a higher accuracy. It is generally accepted that the C-index of less than 0.7 suggests no improvement in model performance [ 24 ]. In calibration curve, the 45-degree line represents optimal predictions, and it illustrates how far the predicted probabilities of this nomogram are from actual observations.…”
Section: Methodsmentioning
confidence: 99%
“…The C-index ranges from 0.0 to 1.0, with the higher value indicating a higher accuracy. It is generally accepted that the C-index of less than 0.7 suggests no improvement in model performance [ 24 ]. In calibration curve, the 45-degree line represents optimal predictions, and it illustrates how far the predicted probabilities of this nomogram are from actual observations.…”
Section: Methodsmentioning
confidence: 99%
“…Although progress has been made in therapeutic strategies, and early detection and clinical management have improved its prognosis, GC remains a complex clinical challenge, with the majority of patients being diagnosed during the later stages of the disease (2,3). Previously, it was reported that the aberrant expression of specific biomarkers was related to cancer development and a worse prognosis, and that some biomarkers affected the sensitivity of cancer to chemotherapeutic drugs (4). Therefore, it is of great benefit to identify novel biomarkers characterized by high sensitivity as well as high specificity that can be used as predictors for GC diagnosis and precise treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As cancer is the result of the accumulation of adverse disease-related molecular events, it is reasonable to stratify patients according to genetic alterations in one or more genes. This has become an important factor in clinical intervention [ 1 , 2 ]. However, while a number of cancer biomarkers for molecular diagnosis have been described recently, the specificity and diagnostic capacity of currently available biomarkers are limited [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%